2015
DOI: 10.1128/jb.00314-15
|View full text |Cite
|
Sign up to set email alerts
|

AraR, an l -Arabinose-Responsive Transcriptional Regulator in Corynebacterium glutamicum ATCC 31831, Exerts Different Degrees of Repression Depending on the Location of Its Binding Sites within the Three Target Promoter Regions

Abstract: In Corynebacterium glutamicum ATCC 31831, a LacI-type transcriptional regulator AraR, represses the expression of L-arabinose catabolism (araBDA), uptake (araE), and the regulator (araR) genes clustered on the chromosome. AraR binds to three sites: one (BS B ) between the divergent operons (araBDA and galM-araR) and two (BS E1 and BS E2 ) upstream of araE. L-Arabinose acts as an inducer of the AraR-mediated regulation. Here, we examined the roles of these AraR-binding sites in the expression of the AraR regulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…l ‐arabinose utilization in most C glutamicum strains require the heterologous expression of l ‐arabinose catabolism genes from E. coli, except for C. glutamicum ATCC 31831, which has a functional gene cluster for l ‐arabinose utilization, including arabinose transporter ( araE ), arabinose isomerase ( araA ), ribulokinase ( araB ), and ribulose 5‐phosphate 4‐epimerse ( araD ) (Fig. ) . The heterologous expression of l ‐arabinose catabolism genes from E. coli resulted in the production of 5.44 g L −1 L ‐glutamate, 8.04 g L −1 L ‐lysine, 11.8 g L −1 L ‐ornithine, and 4.36 g L −1 L ‐arginine (Table ) …”
Section: Utilization Of Alternative Carbon Sources For the Productionmentioning
confidence: 99%
“…l ‐arabinose utilization in most C glutamicum strains require the heterologous expression of l ‐arabinose catabolism genes from E. coli, except for C. glutamicum ATCC 31831, which has a functional gene cluster for l ‐arabinose utilization, including arabinose transporter ( araE ), arabinose isomerase ( araA ), ribulokinase ( araB ), and ribulose 5‐phosphate 4‐epimerse ( araD ) (Fig. ) . The heterologous expression of l ‐arabinose catabolism genes from E. coli resulted in the production of 5.44 g L −1 L ‐glutamate, 8.04 g L −1 L ‐lysine, 11.8 g L −1 L ‐ornithine, and 4.36 g L −1 L ‐arginine (Table ) …”
Section: Utilization Of Alternative Carbon Sources For the Productionmentioning
confidence: 99%
“…This identification is based on changes in their affinity for binding to target operon sequences, alterations in their interactions with other cellular components, or shifts in their capability to form dimer, trimer, or tetramer structures (Ottilie et al 2022 ; Phaneuf et al 2020 ). araR as a GntR family member regulates of carbon catabolism not only of B. subtilis but also other microorganisms (Correia et al 2014 ; Kuge et al 2015 ). Low DNA binding affinity to the arabinose operon was caused by a non-synonymous nucleotide substitution location in araR H226R close to the arabinose binding site on the C-terminal domain (Franco et al 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, C. glutamicum ATCC31831 with the ability to grow on L-arabinose was discovered by random screening. Analysis of the genome of this strain suggested that genes associated with arabinose utilization were included in the araBAD operon, which is negatively controlled by the transcription factor AraR (Kuge et al, 2015). In addition, simultaneous utilization of L-arabinose and D-glucose in C. glutamicum ATCC31831 indicated that carbon metabolism repression was ineffective against arabinose in this strain (Kawaguchi et al, 2009).…”
Section: Arabinosementioning
confidence: 96%